PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR GEOGRAFI PESERTA DIDIK SMAK SINT CAROLUS KUPANG - Soba, Maria Monika Seli; Sunimbar, Sunimbar; Pamungkas, Bella Theo Tomi (Universitas Nusa Cendana, 2022)
The purpose of this research to find out whether there is an effect of the project-based learning model on the learning outcomes of Geography students at SMAK Sint Carolus Kupang. This type of quasi-experimental research with nonequivalent control group research design. The population of this study was all students of class XI IPS. Which consists of 2 classes total 36 students. The class XI IPS 1 student with a total of 18 people as the experimental class and students in class XI IPS 2 with a total of 18 people as the control class. The sampling technique used a saturate sampling technique. Data taken by test and documentation techniques. Data analyzed by simple linear regression. Previously the data were tested for normality, homogeneity test, and linearity test. The results showed that (1) there was an influence in the application of the project-based learning model on student learning outcomes with the results of simple linear regression analysis obtaining a significant value on the model item of 0.000 <0.05. (2) Student learning outcomes have increased with the application of project-based learning models. (3) This is evidenced by the difference in the average learning outcomes of students who achieve KKM in learning with project-based learning which is 94.4% higher than the percentage of students who achieve KKM in learning with conventional models which only reaches 66.6 %.